Na0.25Sr0.5Bi0.25TiO3 relaxor ferroelectric ceramic with greatly enhanced electric storage property by a B-site ion doping. Issue 8 (1st June 2020) - Liu, Gang; Dong, Jia; Zhang, Leiyang; Yu, Linjiang; Wei, Fangbin; Li, Yang; Gao, Jinghui; Hu, Jinzhu; Yan, Yan; Li, Quan; Yu, Kun; Jin, Li
Abstract : A B-site acceptor doping strategy has been employed to fabricate Na0.25 Sr0.5 Bi0.25 TiO3 (NSBT- x M) relaxor dielectric ceramics for the purpose of obtaining predominant energy storage properties for pulsed power capacitor applications. MgO was selected as the acceptor additive, and the corresponding ceramics were designed and prepared by traditional preparation method of electronic bulk ceramic. The influence of MgO on the micro structure, surface micromorphology, the variation of dielectric properties and storage of electrical energy, and also the mechanism of the NSBT- x M samples were deeply and systematically studied. The substitution of Ti 4+ by Mg 2+ at B-site induces point defects companied with defect diploe P D, which influences the electrical properties dramatically. Appropriate amount of MgO can significantly increase the electrical breakdown strength and reduce P r, which is conducive to the improvement of energy storage performance. Particularly, the NSBT-0.25 M sample exhibits both high W rec (2.06 J/cm 3 ) and excellent efficiency (84%) spontaneously. It also exhibits fantastic frequency stability, fatigue endurance, and excellent charge and discharge performance.